Considering Urban Air Pollution in Travel Choice Modeling and Its Application to Logit Model in Nakhon Pathom - Mekin, Thanakorn (Srinakharinwirot University Engineering Journal, 2020)
Air pollution especially the problem particulate matter smaller less than 2.5 microns (PM2.5), which is the main problem affecting public health of commuter travelers. This research aims to develop logit model of travel choice in urban area considering air pollution factor using multinomial logit model and nested logit model. The result shows the model of travel behavior in Nakhon Pathom urban area. There are 4 factors affecting travel choice (significance level of 99 percent): travel cost, service frequency, waiting time and travel time. Based on household income, the high-income level prefers to choose the low-particulate matter vehicle (the low PM vehicle). Travel cost of this group is higher than others. If the cost of traveling increases, people are less likely to choose the low PM vehicle in cabin. Considering to air pollution, this research provides useful information for improving mass transit in urban area. Government should provide the low PM vehicle with proper fare rate which is not effect to low income travelers.